Prevalence of B-Thalassemia Carriers Among a Cohort of University Students in Hawler Province of Iraqi Kurdistan - A. Alnakshabandi, Abdulkadir; A. Muhammad, Huda (Iraqi Journal of Pharmaceutical Sciences, 2017)
A representative sample of a thousand volunteer university students was screened for evidence of thalassemia minor.Complete blood counts using automated blood cell analysers and blood smears were examined. Patients having anemia, abnormal red cell indices or morphological features of thalassemia minor like hypochromia, microcytosis, target cells erythrocytosis and family history of thalassemia were then investigated for determination of HbA2 & HbF levels. Estimation of hemoglobin A2 was performed by micro-column chromatography while HbF was done using alkali denaturation. Seventy seven out of the thousand samples tested positive for thalassemia minor. They all showed a hemoglobin A2 of more than 3.6 percent and higher, associated in most of the cases with mild anemia, erythrocytosis and hypochromic microcytic red cells. We reached to the conclusion that the prevalence of thalassemia minor in our community, represented at college students at fertile age, to be 7.7%. We hope that similar figures could be made available in the future for the rest of Kurdistan and the bigger Iraq so that a national figure could be presented to the world literature.Key word : Î²-Thalassemia , hemoglobin A2 , hemoglobin